DETERMINASI PENYALURAN KREDIT BANK PEMBANGUNAN DAERAH DI INDONESIA - Alif Taufik Elfari; Perwito; Amelia Purwanti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This research has the point of examining the components of the determination ofcredit distribution at Regional Development Banks in Indonesia. The sample used is10 of 26 Regional Development Banks (RDB) in Indonesia. This is due to thelimitations of several Banks which have not distributed their total budget reports.This study uses a quantitative strategy by utilizing the SPSS application which iscarried out with various multiple linear regression analysis methods in which thereare tests, including the classical assumption test, the F test to determine theregression model test, and the t-test for measurement used to test the hypothesis. Thefactors obtained are CAR, TPF, NPL, and ROA affect credit distribution